The Issue of the UK’s Pakistani Community Acculturation - Ulyana V. Klimenko (Научно-аналитический вестник Института Европы РАН)
The article is dedicated to the analysis of a number of features inherent in the UK’s Pakistani community, which manifest in the social and cultural life of the country, based on the research conducted by British sociologists in the time span from 2010 to 2024. The article examines the approaches British Pakistani people take in respect to their identity, emphasizes the importance of personal contacts and the creation of their own self in spaces which are used to exchange experience and which are not directly related to the home and business environment. The emphasis is placed on the complexity and mosaicism of the UK’s Pakistani diaspora members’ identity, as well as on the importance of using art as an instrument of intercultural dialogue. There is a prospect of even greater divergence of British Pakistanis’ points of view in the future, however, the general trend of their acculturation is positive, and at the moment their activity both in the media (television, radio) and in everyday life has slightly increased compared to previous decades.